Effects of Statin Therapy on the Risk of Intracerebral Hemorrhage in Korean Patients with Hyperlipidemia - Jung, Minji; Lee, Sukhyang (Pharmacotherapy, 2019)
Study Objective: Statins are widely used for primary and secondary prevention of cardiovascular and cerebrovascular disease. Several large randomized trials have suggested that statins might increase the risk of intracerebral hemorrhage (ICH); studies have also shown interethnic variability in responses to statins. This study aimed to determine the association between statin use and the risk of ICH in patients with hyperlipidemia among a Korean population. Design: Population-based, retrospective cohort study. Data Source: Korean National Health Insurance Service–National Sample Cohort database (2002–2015). Patients: A total of 313,368 patients, aged 40–85 years, without a history of hemorrhagic stroke were included after being diagnosed with hyperlipidemia between January 2003 and December 2013 (for follow-up through December 2015). Of those, statin users were compared with nonusers by using propensity score matching in a 1:1 ratio (21,797 in each group). The study groups were matched for age, sex, Charlson Comorbidity Index score, follow-up duration, comorbidities, and concurrent medications. Measurements and Main Results: The primary endpoint was occurrence of an ICH event. Secondary endpoints were mortality (all-cause, major adverse cardiovascular and cerebrovascular event related, and stroke related) and outcomes after ICH (e.g., recurrent ICH and mortality after primary ICH event). The Cox proportional hazard model was used to evaluate the ICH risk of statins. Subgroup analyses were performed based on ICH-related risk factors. During a mean follow-up period of 6.4 years, ICH occurred in 456 of the 43,594 patients (1.05%). Statin use was significantly associated with a decreased ICH risk (adjusted hazard ratio [aHR] 0.78, 95% confidence interval [CI] 0.65–0.94). Compared with nonusers, statin users showed significantly lower all-cause mortality (aHR 0.61, 95% CI 0.57–0.64), cardiovascular and cerebrovascular disease-related mortality (aHR 0.75, 95% CI 0.65–0.85), and stroke-related mortality (aHR 0.69, 95% CI 0.54–0.88). No significant differences in recurrence and mortality after an ICH event were noted between study groups. Conclusion: Statin therapy was associated with a decreased ICH risk and improvements in ischemic cardiovascular and cerebrovascular outcomes in Korean patients with hyperlipidemia. Further large-scale clinical studies are needed to clarify the impact of statins on the risk of developing ICH.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cerebral Hemorrhage; Cohort Studies; Databases, Factual; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hyperlipidemias; Male; Middle Aged; Republic of Korea; Retrospective Studies; cohort study; hemorrhagic stroke; intracerebral hemorrhage; statin